Improving Teacher Competence through Digital Technology-Based Learning - Mainudin, Mainudin; Khozin, Khozin; Haris, Abdul (ISTAWA, 2023)
This research aims to explain teacher competency by utilizing digital technology as a learning tool for Islamic religious education. Contribute to developing innovative teaching and increase teacher competency in facing technological challenges in the digital era. The method used is qualitative with a case study approach at the Sumbawa Islamic Pharmacy Vocational School. Data collection techniques were carried out using interviews, observation and documentation studies. The analysis uses qualitative description. The research found that the Islamic education learning process using e-learning affected student learning outcomes. Learning with a blended-learning system, namely a combination of face-to-face and distance learning or offline and online. In the learning implementation stage, Islamic education teachers have carried out essential settings related to using digital e-learning technology, including needs analysis activities, creating instructional designs, steps of using and developing e-learning, and evaluation.